Centrality and energy dependence of rapidity correlation patterns in relativistic heavy ion collisions - Le, Tian (天乐); Xu, Ming-Mei (明梅 许); Wu, Yuan-Fang (元芳 吴) (Chinese physics C, 2011)
The centrality and energy dependence of rapidity correlation patterns are studied in Au+Au collisions by using AMPT with string melting, RQMD and UrQMD models. The behaviors of the shortrange correlation (SRC) and the long-range correlation (LRC) are presented clearly by two spatial-position dependent correlation patterns. For centrality dependence, UrQMD and RQMD give similar results as those in AMPT, i.e., in most central collisions, the correlation structure is flatter and the correlation range is larger, which indicates a long range rapidity correlation. A long range rapidity correlation showing up in RQMD and UrQMD implies that parton interaction is not the only source of long range rapidity correlations. For energy dependence, AMPT with string melting and RQMD show quite different results. The correlation patterns in RQMD at low collision energies and those in AMPT at high collision energies have similar structures, i.e. a convex curve, while the correlation patterns in RQMD at high collision energies and those in AMPT at low collision energies show flat structures, having no position dependence. Long range rapidity correlation presents itself at high energy and disappears at low energy in RQMD, which also indicates that long range rapidity correlations may come from some trivial effects, rather than the parton interactions.